Proportion of Extrapulmonary MDR-TB Confirmed by GeneXpert® in Dr. Hasan Sadikin General Hospital, West Java, Indonesia Year 2012–2021 - Dhestina, Winnery; Santoso, Prayudi; Sahiratmadja, Edhyana (Indonesian Journal of Tropical and Infectious Disease, 2022)
As the third-highest country with tuberculosis (TB) incidence worldwide in 2020, Indonesia has increasing TB cases resistant to various anti-TB therapy or multidrug-resistant (MDR)-TB, and ranked fifth for its high incidence reported in Global Tuberculosis Report 2020. Moreover, extrapulmonary TB (EPTB) is rising, and data studies on EPTB with MDR-TB in Indonesia are scarce. This study aimed to explore the proportion of extrapulmonary MDR-TB among TB cases in Dr. Hasan Sadikin General Hospital Bandung, West Java, Indonesia. A descriptive retrospective and cross-sectional study design were conducted, retrieving medical records from all suspect MDR-TB adult patients examined by GeneXpert®, at Dr. Hasan Sadikin General Hospital Bandung, West Java period 2012–2021. Those with EPTB were further analyzed, and the demographic data was collected as well as clinical history, behavioral history, sites of extrapulmonary MDR-TB, and drug resistance. Of a total 7,013 TB cases, 1,900 (27.1%) were MDR-TB cases, of whom 0.08% (n6) were extrapulmonary MDR-TB cases and 0.16% (n11) were combined with PTB. The main characteristics of cases with extrapulmonary MDR-TB were median age 27-year-old (range 25–34), male gender (64.7%), underweight BMI (84.6%), and predominantly were primary cases (35.3%). The anti-TB drug resistance in MDR-TB were pre-XDR-TB (11.7%), XDR-TB (5.6%), MDR-TB (42%), and RR-TB (40.7%). Although the proportion of extrapulmonary MDR-TB among all TB cases is small (0.2%), this disease can't be ignored and has a great potential to be explored. Most of them are rifampicin-resistant. Further studies need to include a larger population to have more overview of MDR-TB with EPTB.